2008
DOI: 10.21000/jasmr08011352
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Chitin and Organic Substrates on the National Tunnel Waters in Blackhawk, Colorado for Manganese Removal

Abstract: Abstract:The National Tunnel is a part of the Central City / Idaho Springs Superfund site. Because passive treatment is an important possibility for removal of contaminants from the water, the USEPA and the Colorado Division of Public Health and Environment (CDPHE) have been sponsoring a bench-scale study of different organic substrates for sulfate-reducing bioreactors (SRBRs). The substrates being tested include ethanol, woodchips and hay, woodchips and corn stover, and crab-shell chitin. After 6-18 months of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 11 publications
(16 reference statements)
1
14
1
Order By: Relevance
“…In recent studies, crab-shell chitin has shown relatively high efficiency to remove Mn under reducing conditions from MIW in both laboratory and field studies [7][8][9][10]. This efficient acidity and metal removal may be attributed to the dissolution of chitin-associated carbonates, which are naturally present in the shells of crabs and other crustaceans to provide structural strength [11].…”
Section: Introductionmentioning
confidence: 99%
“…In recent studies, crab-shell chitin has shown relatively high efficiency to remove Mn under reducing conditions from MIW in both laboratory and field studies [7][8][9][10]. This efficient acidity and metal removal may be attributed to the dissolution of chitin-associated carbonates, which are naturally present in the shells of crabs and other crustaceans to provide structural strength [11].…”
Section: Introductionmentioning
confidence: 99%
“…Designs that increase the depth of water over the organic layer to a meter or more would be expected to increase flushing effectiveness relative to shallow-water designs, but that expectation has not been tested experimentally. The decreasing effectiveness of Organic substrate material References Easily-available materials-sugars, starch, proteins, oils, liquids Edible oil substrate (EOS), mainly emulsified soybean oil, worked well in lab tests Borden (2004, 2005) Cheese whey added to reactors containing cow manure and pine sawdust greatly improved effectiveness Drury (1999) Ethanol was more satisfactory than cellulosic materials at low temperature Buccambuso et al (2007) Methanol was effective in supporting sulfate reduction of lignite pit water Glombitza (2001) Ethanol and methanol were effective in removing Fe at low pH Tsukamoto et al (2004) Glycerol-methanol waste from production of biodiesel fuel was capable of extensive sulfate reduction Zamzow et al (2006) Crab shell chitin was highly effective Daubert and Brennan (2007), Newcombe and Brennan (2008) Chitin was much more effective than lactate or compost Robinson-Lora and Brennan (2010) Chitin, hay and corn with 20-30 % limestone were more effective than ethanol; chitin was very effective for Mn removal Venot et al (2008) Mussel shells were very effective in AMD treatment either alone or mixed with organic materials Trumm and Ball (2014), Uster et al (2015) Cellulose and hemicellulose materials-manures, compost 85 % pea gravel and 15 % leaf compost worked well for at least 2 years McGregor et al (2000) Municipal compost from wastewater treatment was poor Gibert et al (2004) Sewage sludge and rye grass was better than either alone Harris and Ragusa (2001) Organic soil and ryegrass accomplished good treatment Harris and Ragusa (2001) Mushroom compost, waste paper sludge, and decayed oak chips were better than fresh oak chips and organic soil Cow manure and hay with 30 % limestone were more effective than sawdust and wood chips Smart et al (2008) Composted cow manure mixed with ceramic pellets was effective in removing metals by adsorption Willow and Cohen (2003) Mixtures of materials were better than pure leaf mulch, sheep manure, sewage sludge or cellulose Waybrant et al (1998) Decayed wood shavings, straw, manure and spent brewery grains were very effective in treating low pH, high Fe AMD Romanek (2002a, 2002b) Lignin-hay, straw, woody materials Alfalfa hay was better than straw or timothy hay Bechard et al (1994) Wood shavings, pine bark, and compost plus limestone or mussel shell mixtures worked satisfactorily in lab tests…”
Section: Flushing Systems For Biological Passive Systemsmentioning
confidence: 99%
“…In laboratory microcosms tests using spent mushroom compost, sodium lactate, and crab-shell chitin, the latter was the only substrate capable of promoting significant Mn removal in both live and killed systems (>73%, Robinson-Lora and Brennan, 2008). In field studies, enhanced Mn removal (86%) was observed with crab-shell chitin, compared to other substrates (50% for ethanol, wood chips/hay, wood chips/corn stover; Venot et al, 2008).…”
Section: Introductionmentioning
confidence: 96%